2018
DOI: 10.1111/epi.14057
|View full text |Cite
|
Sign up to set email alerts
|

Depression comorbidity in epileptic rats is related to brain glucose hypometabolism and hypersynchronicity in the metabolic network architecture

Abstract: This study revealed relevant alterations in glucose metabolism and the metabolic network among the brain regions of interest for both epilepsy and depression pathologies. Thus it seems that depression in epileptic animals is associated with a more diffuse hypometabolism and altered metabolic network architecture and plays an important role in chronic epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Thus, our results suggest that following epilepsy manifestation, hippocampal hypometabolism may constitute a marker of neurobehavioral alterations, as opposed to a marker of seizure severity. A recent study in the chemically induced pilocarpine post‐SE model has similarly described a correlation between reduced [ 18 F]FDG uptake and a depressivelike phenotype . The authors reported a global reduction in [ 18 F]FDG uptake as opposed to the region‐specific reduction indicated by our results.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, our results suggest that following epilepsy manifestation, hippocampal hypometabolism may constitute a marker of neurobehavioral alterations, as opposed to a marker of seizure severity. A recent study in the chemically induced pilocarpine post‐SE model has similarly described a correlation between reduced [ 18 F]FDG uptake and a depressivelike phenotype . The authors reported a global reduction in [ 18 F]FDG uptake as opposed to the region‐specific reduction indicated by our results.…”
Section: Discussionsupporting
confidence: 62%
“…With this protocol, we activate not only cortical zones but also inner structures that are essential in cognitive processes. It could be useful in order to modulate brain networks that could be altered in some experimental models [48] that aim to emulate clinical alterations in human population. In addition, we have proved that the rTMS effects of 1 day of stimulation (100 Hz; 10 sessions; 30000 pulses) can endure up to 48 hours, leading to a brain metabolic activity enhancement in cortical regions distant to the stimulation focus, suggesting that rTMS effects have an impact into brain functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that hippocampal dysfunction may be one of the leading factors in the development of depression, rather than the frequency of seizure or degree of disability [1113, 41, 56]. In 2011, Gonçalves and Cendes demonstrated that patients with longer duration of epilepsy showed an increased risk of depression, however there was no association between seizure frequency and depression [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, clinical and experimental studies evidenced neurobiological mechanisms that could linkage epilepsy and depression symptoms, such as differences in neurotransmitters [12] and alterations in brain glucose metabolism and metabolic network in regions related to the pathophysiology of both epilepsy and depression [13]. Another factor that could contribute to depressive and anxiety symptoms in TLE is the hemisphere of epileptogenic focus, but this still remains uncertain, with studies pointing to prevalence of interictal depression in left-sided seizure foci [14,15], while others showing a tendency for greater depressive symptoms in presurgical right-sided seizure foci patients [14,15].The most frequent way to evaluate depressive and anxiety symptoms in epilepsy patients is by using scales and inventories that provide a quantitative measure of recurrent and severity of mood symptomatology experienced by the patients [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation